Non-verbal communication of English speaking skills in single-sex classroom management - Hardianti Lestari Hamsah (International Journal of Humanities and Innovation (IJHI), 2018)
This research explores to what extent the eleventh year's students of the single-sex classroom management have mastered the English-speaking skills regarding eye contact, enthusiasm, and confidence. This research exposes to what extent the eleventh year's students of the single-sex classroom management have mastered the English-speaking skills regarding eye contact, enthusiasm, and confidence. This study used a qualitative method by descriptive design. The procedure of collecting data the researcher used classroom observation, teacher interview, and student’ focus discussion group. In collecting data and analysis technique the researcher measured from three aspects namely students ‘confidence, eye contact, and enthusiasm. Each aspect was described. This study revealed that the female students who have already been in the single-sex classroom have high confidence, convey strong enthusiasm and maintain eye contact well while speaking English. Therefore, we can say that the eleventh year’s students of the single-sex classroom management have mastered the English-speaking skills regarding eye contact, enthusiasm, and confidence in which the researcher in a single-sex classroom has done the criteria.